Differential Expression of Genes of the Calvin–Benson Cycle and its Related Genes During Leaf Development in Rice. (27th November 2015) - Yamaoka, Chihiro; Suzuki, Yuji; Makino, Amane
Abstract : To understand how the machinery for photosynthetic carbon assimilation is formed and maintained during leaf development, changes in the mRNA levels of the Calvin–Benson cycle enzymes, ribulose-1, 5-bisphosphate carboxylase/oxygenase (Rubisco) activase and two key enzymes for sucrose synthesis were determined in rice ( Oryza sativa L.). According to the patterns of changes in the mRNA levels, these genes were categorized into three groups. Group 1 included most of the genes involved in the carboxylation and reduction phases of the Calvin–Benson cycle, as well as three genes in the regeneration phase. The mRNA levels increased and reached maxima during leaf expansion and then rapidly declined, although there were some variations in the residual mRNA levels in senescent leaves. Group 2 included a number of genes involved in the regeneration phase, one gene in the reduction phase of the Calvin–Benson cycle and one gene in sucrose synthesis. The mRNA levels increased and almost reached maxima before full expansion and then gradually declined. Group 3 included Rubisco activase, one gene involved in the regeneration phase and one gene in sucrose synthesis. The overall pattern was similar to that in group 2 genes except that the mRNA levels reached maxima after the stage of full expansion. Thus, genes of the Calvin–Benson cycle and its related genes were differentially expressed during leaf development in rice, suggesting that such differential gene expression is necessary for formation and maintenance of the machinery of photosynthetic carbon assimilation.